The Influence of Social Media Marketing on Purchasing Decisions Through Word of Mouth in the Dunkin Donut Company - Aghni Aulia Aziz; Aliman Wiranta (Medikun Publisher, 2024)
The purpose of this research is to determine the influence of social media marketing on purchasing decisions, to determine the influence of social media marketing on word of mouth, to determine the influence of word of mouth on purchasing decisions, to determine the influence of social media marketing on purchasing decisions through word of mouth on Dunkin Donuts. The population in this research is customers who make purchases at Dunkin Donut, where the sample size is 100 via the GPower application. The data collection technique used in this research is a questionnaire via Google Form. The analysis technique used in this research is the Strucural Equiation Model with a Partial Least Square approach. From the test results Social Media Marketing has a positive and significant effect on Purchasing Decision, Social Media Marketing has a positive and significant effect on Word of Mouth, Word of Mouth has a positive and significant effect on Purchasing Decision, Social Media Marketing has a positive and significant effect on Purchasing Decision mediated by Word of Mouth